Optimasi Kemiringan Sel Surya untuk Meningkatkan Daya Keluaran: Pendekatan Kontekstual dalam Pembelajaran Energi Terbarukan di SMA - Eni Mulayani; Muhammad Subhan (Universitas Nggusuwaru, 2026)
This study aims to investigate the optimal tilt angle of solar cells to maximize power output and to evaluate its effectiveness as a contextual learning approach for renewable energy topics in high school. Determining the optimal angle is crucial as solar radiation intensity depends on the sun's position relative to the panel's surface. The research employs a quantitative experimental approach. The experiment involved students measuring voltage, current, and power on a 12 Volt 10 Watt solar panel at tilt angles of 0°, 10°, 20°, 30°, 40°, and 50°. Experimental results demonstrated that the maximum power output of 7.22 Watts was achieved at a 20° tilt angle. Graphical analysis of current versus power (Figure 1) and tilt angle versus power (Figure 2) confirmed that angle deviation from the optimal point directly impacts photon absorption and electrical current, leading to a drastic power drop to 4.20 Watts at a 50° angle. Integrating this experiment into learning has proven capable of concretizing energy conversion concepts scientifically. This contextual approach is recommended to support meaningful science learning